2004
DOI: 10.1300/j148v21n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Motor Learning of a Functional Motor Task

Abstract: Purpose: The purpose of this study was to compare the ability of older and younger adults to learn a functional motor task following a single session of directed practice. The task under investigation was the use of a standard walker to get into the passenger side of a fourdoor sedan using a specific procedure.Methods: Thirty younger community-dwelling adults (aged 20-35), and thirty older community-dwelling adults (aged 61-93), with no diagnosis of dementia and no prior experience using a walker were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A decline of motor performance with age has been observed in many previous studies with a variety of movement tasks (Voelcker-Rehage 2008 ; Voelcker-Rehage and Willim-czik 2006 ; Etnier 1998 ; Tunney et al. 1998 ). Studies have also found that aging slows the rate of motor learning (Swinnen 1998 ; Brosseau et al 2007 ; Wishart et al.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A decline of motor performance with age has been observed in many previous studies with a variety of movement tasks (Voelcker-Rehage 2008 ; Voelcker-Rehage and Willim-czik 2006 ; Etnier 1998 ; Tunney et al. 1998 ). Studies have also found that aging slows the rate of motor learning (Swinnen 1998 ; Brosseau et al 2007 ; Wishart et al.…”
Section: Discussionmentioning
confidence: 66%
“…1998). Studies have also found that aging slows the rate of motor learning (Swinnen 1998; Brosseau et al 2007; Wishart et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, older adults tend to learn new motor skills at a slower rate and to a lesser extent than young adults. 10,11 Thus, older patients may require more training to induce a therapeutic effect (ie, efficacy). Furthermore, if more task-specific training is needed for older patients, then they must be able to tolerate these extended training sessions (ie, feasibility).…”
Section: Introductionmentioning
confidence: 99%